Atomic wires on substrates: physics between one and two dimensions - Pfnür, Herbert; Tegenkamp, C.; Sanna, S.; Jeckelmann, E.; Horn-von Hoegen, M.; Bovensiepen, U.; Esser, N.; Schmidt, W. G.; Dähne, M.; Wippermann, S.; Bechstedt, F.; Bode, M.; et al. (Surface science reports, 2024)
Wires having a width of one or two atoms are the smallest possible physical objects that may exhibit one-dimensional properties. In order to be experimentally accessible at finite temperatures, such wires must stabilized by interactions in two and even three dimensions. These interactions modify and partly destroy their one-dimensional properties, but introduce new phenomena of coupling and correlation that entangle both charge and spin. We explore this fascinating field by first giving an overview of the present status of theoretical knowledge on 1D physics, including coupling between chains and to the substrate, before we set out for experimental results on ordered arrays of atomic wires on both flat and vicinal Si(111) surfaces comprising Si(111)-In, Si(hhk)-Au, Si(557)-Pb, Si(557)-Ag, on Ge(001)-Au and of rare earth silicide wires. While for these systems structural, spectroscopic and (magneto-)conductive properties are in the focus, including temperature- and concentration-induced phase transitions, explicit dynamics on the femto- and picosecond time scales were explored for the modified Peierls transition in indium chains on Si(111). All these systems are characterized by strong correlations, including spin, that are extended over whole terraces and partly beyond, so that small geometric changes lead to large modifications of their electronic properties. Thus this coupling in one (1D), two (2D) (and even three) dimensions results in a wealth of phase transitions and transient quasi-1D conductance. As extremes, modified quasi-1D properties survive, as in the Si(111)-In system, whereas strong Fermi nesting results in entanglement of spin and charge between terraces for Si(557)-Pb, so that spin orbit density waves across the steps are formed.
Online verfügbar: 7. Mai 2024, Artikelversion: 28. Mai 2024
Gesehen am 02.12.2024